2008
DOI: 10.1111/j.1365-277x.2007.00846.x
|View full text |Cite
|
Sign up to set email alerts
|

Food portion weights in primary and secondary school lunches in England

Abstract: The results provide a good representation of typical portion weights for different foods and food groups in primary and secondary schools in England. Portion size is one factor that determines nutrient intake. New standards for school lunches are both nutrient and food-based. Guidance on portion weights will help to ensure that pupils consume the correct balance of foods to obtain the recommended nutrient intake. The present findings complement and extend existing guidance on portion sizes for pupils in school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 0 publications
2
18
0
Order By: Relevance
“…This method has previously been used and validated with children aged 9–10 years, correlations between observed and reported nutrient and energy intake ranged from 0.78 to 0.94 [38]. Estimated weights of portions were then calculated using published values, including those specific to children [39], [40]. Based upon a recommended portion size of 40 grams for school age children [41] and public health guidelines of 5 portions per day [15], achievement of recommendations for fruit and vegetable intake was defined as ≥200 grams/day.…”
Section: Methodsmentioning
confidence: 99%
“…This method has previously been used and validated with children aged 9–10 years, correlations between observed and reported nutrient and energy intake ranged from 0.78 to 0.94 [38]. Estimated weights of portions were then calculated using published values, including those specific to children [39], [40]. Based upon a recommended portion size of 40 grams for school age children [41] and public health guidelines of 5 portions per day [15], achievement of recommendations for fruit and vegetable intake was defined as ≥200 grams/day.…”
Section: Methodsmentioning
confidence: 99%
“…Although chips are not specifically part of the current school lunch recommendation, they were considered here as such deep-fried, high-fat foods have been implicated as a potential contributor to obesity (23) and their presence on school menus has been associated with higher BMI among pupils (21) . Unsurprisingly, the school meal group consumed more chips, both at lunchtime and over the whole day, although the average weight consumed at lunchtime is quite small; 23?0 g for a school meal, which equates to roughly a portion every 3?9 d, based on a typical portion size of 90 g (13) . Some chips also appeared to be eaten by the packed lunch group at school lunchtime.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that school meal eaters consumed more starchy foods compared with packed lunch eaters, although a lower proportion of that was from bread. Neither lunch group consumed a full daily portion of starchy foods (based on average portion sizes of 80 g of rice and 100 g of mashed potato (13) ). Starchy foods are promoted as a means of satiating hunger without excessive consumption of fat (2) , and higher consumption may help children meet the SFT recommendation of at least 50 % of food energy coming from carbohydrates (22) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For each food or drink recorded, weights of the portions consumed were approximated using published values for children (Crawley, 2002, Davies et al., 2008, Wrieden et al., 2008). Diaries were coded by a team of researchers at Medical Research Council Human Nutrition Research (Cambridge, UK) using the Diet-In Nutrients-Out (DINO) system, a state of the art integrated dietary assessment system, which uses continually updated British food composition data.…”
Section: Methodsmentioning
confidence: 99%